2005
DOI: 10.1167/iovs.05-0209
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Optic Nerve Capillary Blood Flow Response to Diurnal Variation of Mean Ocular Perfusion Pressure in Early Untreated Primary Open-Angle Glaucoma

Abstract: The mean rim flow did not change during the day, implying that the anterior optic nerve capillary blood flow was autoregulated in both normal subjects and in patients with uPOAG, despite significant changes in IOP and MOPP. However, the regions of greatest diurnal change in rim topography (MTF) had significant diurnal change in capillary blood flow in patients with uPOAG but not in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…This last point probably explains why most studies which reported IOP and BP data had measurements performed the same day. 6,11,26,41,62 Another difficulty in comparing studies may be related to the different definitions of the nocturnal dip, as a decrease of BP between 5% and 10% 26 or between 10% and 20% (our study). 12,20 This may also explain the lowest number of overdipper patients in our study compared with the number in a recent study.…”
Section: Discussionmentioning
confidence: 82%
“…This last point probably explains why most studies which reported IOP and BP data had measurements performed the same day. 6,11,26,41,62 Another difficulty in comparing studies may be related to the different definitions of the nocturnal dip, as a decrease of BP between 5% and 10% 26 or between 10% and 20% (our study). 12,20 This may also explain the lowest number of overdipper patients in our study compared with the number in a recent study.…”
Section: Discussionmentioning
confidence: 82%
“…Under the same experimental conditions and with the same technical limitations of scanning laser Doppler flowmetry, 12,20,25,27,28 the diurnalto-nocturnal changes in ocular blood flow were not statistically different in a group of healthy younger volunteers. Ocular biometric parameters between the older group and the younger group were not different ( Table 1).…”
Section: Discussionmentioning
confidence: 89%
“…[9][10][11][12][13] Previous studies showed that variations in ocular blood flow throughout the diurnal/ wake period were not significant in both younger and older adults. 20,31 One study suggested that ocular blood flow in the optic nerve head decreased at the end of the diurnal/wake period in younger adults. 32 In the present study, we extended the measurement times into the nocturnal/sleep period.…”
Section: Discussionmentioning
confidence: 99%
“…Median flow, however, showed no such relationship. Also, a postprandial drop in MAP and OPP correlated with an increase in flow only in the POAG group, suggesting that the POAG group had insufficient autoregulation [163].…”
Section: Iop Variationsmentioning
confidence: 90%